PATIENT SAFETY DAN MANAJEMEN RISIKO PENGENDALIAN INFEKSI SILANG PADA PRAKTISI KESEHATAN GIGI DAN MULUT: LITERATURE REVIEW - Chyca Selviasari (JURNAL KEPERAWATAN, 2026)
Background: Patient safety is a fundamental component of healthcare quality, including in dental and oral health services. Dental practice involves invasive procedures, exposure to blood and saliva, and the use of sharp instruments, which increase the risk of cross-infection transmission. Objective: to examine patient safety principles and risk management strategies in controlling cross-infection among dental and oral health practitioners. Method: A literature review method was conducted the PICOT method as the framework for formulating the research question. In this study, the PICOT components were defined as follows: P (Population) referred to dental and oral health practitioners; I (Intervention) was the implementation of patient safety and risk management; C (Comparison) represented conventional practice or conditions without standardized risk management implementation; O (Outcome) included the reduction of cross-infection risk, improvement in compliance with patient safety protocols, and enhancement of service quality; and T (Time) referred to articles published within the last ten years. Results: The results indicate that cross-infection control in dental practice is closely related to compliance with standard precautions, risk identification, and the development of a patient safety culture. Risk management approaches, including risk assessment, infection control protocols, and continuous professional training, play a significant role in minimizing adverse events and ensuring safe dental care. This study identifies the relationship between patient safety and cross-infection risk management, based on a literature review comprising 6 (articles) on patient safety, 10 (articles) on cross infection, and 4 (articles) on risk management. Conclusion: Strengthening patient safety systems and risk management practices is essential to improve the quality and safety of dental and oral health services. Keywords: cross-infection control; dental practitioner; patient safety; risk management.